FORMULASI, KARAKTERISASI DAN UJI STABILITAS MIKROEMULSI MINYAK NILAM (Pogostemon cablin Benth.) - Benni Iskandar; Anita Lukman; Raesa Tartilla; Meircurius Dwi Condro Surboyo; Leny Leny (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Patchouli oil contains patchouli alcohol as the main component which is a tricyclic tertiary alcohol sesquiterpene compound that is insoluble in water. Microemulsion is a droplet dispersion technology that combines an insoluble liquid with another liquid. The role of surfactants in helping the dispersion process of microemulsion formulation is by reducing the interfacial tension. Microemulsion is a supersolvents carrier, so that both hydrophilic and lipophilic can be administered through a microemulsion system. The purpose of this study was to formulate patchouli oil into a stable microemulsion preparation. This research was conducted by making 4 preparations of patchouli oil microemulsion containing 5% (F1), 10% (F2), and 15% (F3) patchouli oil, and microemulsion without patchouli oil (F0). Evaluation of microemulsion preparations includes organoleptic test, pH measurement, density determination, viscosity test, freeze and thaw test, centrifugation test, and particle size analysis. The test results showed that the microemulsion containing 5% patchouli oil had the most stable characteristics compared to other formulas.